The Representation of Class Difference Issues among the Oppressed Class in Suzanne Collins’ the Hunger Games Novel (2008) from Marxist Perspective - Wiryani, Ni Made Ayu (Jurnal Penelitian Mahasiswa Indonesia, 2022)
This research aimed at investigating the class difference issues occurred among the oppressed class in Susanne Colllins’ The Hunger Games (2008) using Marxist literary criticism. Using Interactive Model Analisis, this qualitative research revealed two major class difference issues: exploitation and discrimination. The exploitation issue was identified in the form of children exploitation; meanwhile, the discrimination issue was identified in the form of socio-economic discrimination. Those issues appeared due to the three identified factors: poverty, false consciousness, and welfare struggle. Therefore, this research suggested the future research to dig and reveal the social class issue presented in the other novel of The Hunger Games Trilogy.